Socio-Cultural Influences on Stunting Children Aged 24-59 Months: A Cross-Sectional Study in the Bugis Community of Indonesia - Haniarti , Haniarti; Sabriani, Sabriani; Nurlinda, Nurlinda; Fitriani Umar (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2025)
Introduction: Stunting remains a persistent public health challenge in Indonesia, particularly among traditional communities such as the Bugis in Belawae Village. This study investigates the influence of socio-cultural practices on the prevalence of stunting in children under five, focusing on maternal behaviors during pregnancy, breastfeeding, and toddlerhood. The objective is to identify culturally embedded factors that contribute to undernutrition and hinder optimal child development. Method: Employing a cross-sectional design, the study collected data from 112 mothers using structured questionnaires and anthropometric measurements of their children. Socio-cultural practices, such as food taboos, avoidance of colostrum, and early complementary feeding, were examined. Data were analyzed using descriptive statistics and chi-square tests to determine associations between cultural practices and stunting. Results: Findings reveal significant associations between stunting and cultural practices at all developmental stages. Notably, the overall stunting prevalence was 33.9%. the avoidance of nutrient-rich foods during pregnancy and breastfeeding, discarding colostrum, and premature introduction of solid foods were common. These behaviors, shaped by traditional beliefs, contributed to inadequate nutrition during the child’s first 1000 days-a critical window for growth and development. The study also found that maternal education, socioeconomic status, and gender perceptions intersect with cultural norms, influencing feeding decisions and health outcomes. These results align with broader evidence highlighting the role of cultural context in determining child nutrition. Conclusion: This research contributes to the understanding of how culturally driven behaviors affect stunting, emphasizing the need for context-sensitive interventions. Strategies to reduce stunting must integrate cultural competence, promote community engagement, and support respectful behavioral change. Addressing stunting effectively requires public health approaches that balance scientific recommendations with cultural values.